PENGARUH KREATIVITAS, INOVASI DAN TRANSFORMASI DIGITAL TERHADAP KEWIRAUSAHAAN UMKM DI PANGKALPINANG - Indria; Astuti, Nelly; Maharani, Yunita (STIE IBEK Pangkalpinang, 2021)
This research was entitled: “Pengaruh Kreativitas, Inovasi Dan Transformasi Digital Terhadap Kewirausahaan UMKM Di Pangkalpinang.”. The background of this research is based on existing phenomena showing that the competition among MSME is increasing digitally during the pandemic. The purpose of this study was to determine and examine the effect of creativity, innovation and digital transformation towards entrepreneurship, both simultaneously and partially. The method of research is a descriptive quantitative study with a sample size of 100 respondents. This study has three independent variables; creativity, innovation and digital transformation. The dependent variable was labeled as an entrepreneurship. Testing instruments are using validity and reliability tests. The data analysis method used in this study is Multiple Linear Regression Analysis using the F-test along with Simple Linear Regression with T-test. Also the researcher use an analysis of the Coefficient of Determination (R2) in order to provide empirically the ability to explaining the dependent by two independence variables simultaneously. The results of the research on the independent variable creativity (X1) obtained t-count 2.932 > t-table 1.660, innovation variable (X2) with t-count 6,022 > t-table 1.660 and digital transformation variable (X3) with t-count 7,022 > t-table 1.660 Therefore, a creativity has a partial effect towards entrepreneurship, and an innovation has a partial effect towards entrepreneurship. Also, the study stated if digital transformation has a partial a partial effect towards enterpreneurship. The results of the F-test show that F-count 50.485 > F-table 2.70. This means that the independent variables (creativity, innovation and digital transformation) simultaneously has an affect towards the dependent variable (entreprenurship). The test results of the Coefficient of Determination (R2) show Adjusted R-Square 0.600 or in other word, that entrepreneurship variables can be explained by variables creativity, innovation and digital transformation) by 60%. While the remaining 0,400 or 40% can be explained by other variables outside the research variables.